1988
DOI: 10.1139/f88-064
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Tract Evacuation in Northern Squawfish (Ptychocheilus oregonensis)

Abstract: Digestive tract evacuation in northern squawfish (Ptychocheilus oregonensis) (170–1900 g) was studied in fish allowed to feed voluntarily on salmon (4–70 g) at three water temperatures (10, 15, and 20 °C). Squawfish were sacrificed at 1- or 2-h intervals until evacuation approximated 90%. Amount of food evacuated for a given time interval increased approximately three times as the temperature was increased and as the prey weight was increased and two times as the predator weight was increased. The 90% emptying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Using the model of Beyer et al (1988), 90% of a salmonid meal would be evacuated from a 1000 g northern pikeminnow within c. 18 h in April-May (c. 12 C) and within c. 6 h in June-August (c. 19 C). Studies with cod Gadus morhua L. and rainbow trout O. mykiss (Walbaum) have shown that indigestible particles (glass beads and pieces of chitin) may be retained about twice as long as digestible material (Kionka & Windell, 1972;dos Santos & Jobling, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Using the model of Beyer et al (1988), 90% of a salmonid meal would be evacuated from a 1000 g northern pikeminnow within c. 18 h in April-May (c. 12 C) and within c. 6 h in June-August (c. 19 C). Studies with cod Gadus morhua L. and rainbow trout O. mykiss (Walbaum) have shown that indigestible particles (glass beads and pieces of chitin) may be retained about twice as long as digestible material (Kionka & Windell, 1972;dos Santos & Jobling, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Transforming the percentage values by either square root or natural logarithm both provided good linear fits to the data. The negative exponential (natural logarithm) model (y = ae-bx) was chosen because it has been shown to best describe the emptying curve for fishes feeding on relatively low energy diets and ingesting small particles (Jobling 1986(Jobling , 1987 and for other species of stomachless fishes (Grove & Crawford 1980, Persson 1982, Beyer et al 1988. Thus, alimentary tract evacuation rate was calculated for each fish from the linear regression equation:…”
Section: Methodsmentioning
confidence: 99%
“…Flowerdew Beyer et al, 1988;Temming & Andersen, 1994;Andersen, 1998 Ration Cod Gadus morhua, whiting Merlangius merlangus Olson & Boggs, 1986;Bromley, 1987;Bromley, 1988;Rosch, 1987;Elliott, 1991;Singh-Renton & Bromley, 1996 Fish mass at a constant R g Absolute GER Increases Walleye Stizostedion vitreum vitreum Swenson & Smith, 1973;Jobling et al, 1977;Flowerdew & Grove, 1979;Beyer et al, 1988;Hö lker & Temming, 1996 Fish mass at a constant R % Talbot et al, 1984;Olson & Boggs, 1986;Rosch, 1987;Elliott, 1991;Hayward & Weiland, 1998;Hop & Tonn, 1998 Ration Jobling et al, 1977;Flowerdew & Grove, 1979;Rosch, 1987;Rogers & Burley, 1991;…”
Section: Ukmentioning
confidence: 99%